Advanced Topics for End-of-Life Care. (11th November 2018) - Morin, L; Wastesson, J; Agahi, N; Johnell, K
Abstract: This nationwide, longitudinal matched cohort study aimed to investigate the effects of spousal loss on health outcomes and mortality among older adults. Using data from national registries with full-population coverage in Sweden, we included the surviving spouses of older adults (≥65 years) who died in Sweden in 2013–2014, matched 1:1 (sex, age) with married controls. Cases and controls were followed-up for 1 year. The risk of adverse health outcomes was estimated using adjusted Cox proportional hazard regression models with stratification on the matched pairs. We calculated hazard ratios (HR) with 95% confidence intervals (CI). A total of 42 925 bereaved older adults were included and matched with an equal number of married controls. Mean age was 78.4 years (SD= 7.2). All-cause mortality was significantly higher among bereaved older adults (49.2 per 1000 person-years) than among controls (30.7 per 1000 person-years). Adjusted Cox regression showed a risk of 1-year mortality 1.67 (95% CI 1.54–1.81) times higher for bereaved older adults compared with controls. We also found an increased risk of stroke (HR 1.42, 95% CI 1.26–1.60), hip fracture (HR 1.47, 95%CI 1.29–1.67), self-harm (HR 3.87, 95% CI 2.35–6.39), and unplanned hospitalization (HR 1.27, 95% CI 1.23–1.31). Bereaved individuals were at higher risk of nursing home admission (HR 2.03, 95% CI 1.57–2.62). Our findings confirm that bereavement has a significant and rapid impact on both fatal and non-fatal health outcomes among surviving spouses. This demonstrates the need for appropriate support of recently bereaved older adults.